Immune consequences of the spontaneous pro-inflammatory status in depressed elderly patients. - Trzonkowski, P; Myśliwska, J; Godlewska, B; Szmit, E; Łukaszuk, K; Wieckiewicz, J; Brydak, L; Machała, M; Landowski, J; Myśliwski, A (2004)
INTRODUCTION: The aim of the study was to describe the interrelationship between senescence, depression, and immunity. METHODS: We assessed 10 elderly patients with depression and 10 age- and sex-matched controls: before, at one and at six month intervals after the anti-influenza vaccination. Levels of TNFalpha, IL6, ACTH, and cortisol, titres of anti-hemagglutinins and anti-neuraminidases, lymphocytes secreting IFNgamma, IL2, IL4, and IL10, cytotoxicity of NK and CD3+ CD8+ IFNgamma+ cells, anti-CMV antibodies, and CD28- CD57+ lymphocytes known to be associated with the CMV carrier status were evaluated. RESULTS: Higher levels of anti-CMV, higher percentage of the CD28- CD57+ cells, and elevated levels of TNFalpha, IL6, and cortisol concomitant with decreased levels of ACTH and insufficient production of IL10 (which increased the IFNgamma+ /IL10+ ratio) were found in the patients suffering from depression, in comparison to healthy controls. The subjects with depression revealed a low NK cytotoxicity, while a level of CD3+ CD8+ IFNgamma+ cells was comparable between the groups. Although the levels of anti-hemagglutinins and anti-neuraminidases were low in the depressed patients, they reached the protective titres. The majority of these differences disappeared when CMV titres were entered into the analyses as a covariate. DISCUSSION: The results suggest that the elderly depressed patients were characterised by increased exposure to CMV in the past, which could have resulted in a pro-inflammatory profile demonstrated as elevated levels of TNFalpha, IL6 and deficiency of suppressive IL10+ cells. These changes negatively affect humoral and innate response in the depressed patients.